GAMBARAN LENGTH OF STAY BERDASARKAN TINGKAT PRIORITAS DI INTENSIVE CARE UNIT RSUD ULIN BANJARMASIN - Ni Wayan Siti; Ifa Hafifah; Tina Handayani Nasution (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2022)
Patient admitted to the intensive care unit were categorized into four admission indications, namely patients with priority one, two, three and four. Patients classified as priorities three and four have longer ICU care compared to priorities one and two. This study aims to determine the description of the Length of Stay (LOS) based on the priority level in ICU of Ulin Hospital Banjarmasin. The sampling technique in this study used a non-probability sampling with consecutive sampling. The sample in this study amounted to 31 patients. The results showed that the average age value was 41 years. The majority respondents were female, namely 19 people. Most of the patients admitted to the intensive care room at the Ulin Banjarmasin Hospital were priority 1 patients, from 31 people there were 17 patients who entered priority 1 criteria. The longest LOS was the post craniotomy tumor patient with LOS of 22 days. The number of ICU rooms is very limited and is not proportional to patients who neeed treatment in the intensive care unit, so priority criteria are used to determine patients who deserve treatment in the ICU.